(untitled) (Journal of The Colloquium for Information Systems Security Education, 2013)
Current incarnations of cyber competitions emphasize network attack and defense over information assurance. Capturing or defending network assets represents an end, rather than a means to accomplish a broader mission. In this paper we present a cyber competition paradigm focused on assuring a mission. Consistent with traditional engineering competitions, competitors bring their own designed artifacts to the competition to fulfill their assigned mission. Our competition focuses on assuring orders transmitted across a cloud computing environment. We present a framework for the implementation of an assurance based competition and demonstrate the competition through a digital chess game. We distinguish our competition from existing models by awarding points for success in a competition domain distinct from, but coupled to cyberspace.